Pengaruh Brand Awareness dan Social Media Marketing terhadap Keputusan Pembelian Produk Lotion Vaseline - Rizkia Putri Primadhita; Mukhroji Mukhroji (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study was conducted to examine the influence of brand awareness and social media marketing on consumers' purchasing decisions regarding Vaseline body lotion products. A quantitative approach with a causal-associative research design was employed. Primary data were collected through an online questionnaire distributed to Indonesian consumers who had previously purchased or used Vaseline body lotion. The sample consisted of 99 respondents selected using purposive sampling. Data were analyzed using multiple linear regression with IBM SPSS Statistics version 26. The results indicate that brand awareness (B = 0.507; p < 0.001) and social media marketing (B = 0.299; p = 0.003) have positive and significant effects on purchasing decisions. Simultaneous analysis also shows that both variables significantly influence purchasing decisions (F = 62.734; p < 0.001), with brand awareness making the greater contribution. Therefore, strengthening brand awareness and implementing effective social media marketing strategies are important factors in encouraging consumers' purchasing decisions regarding Vaseline body lotion products.